Characterizing and sourcing ambient PM2.5 over key emission regions in China III: Carbon isotope based source apportionment of black carbon. (March 2018) - Yu, Kuangyou; Xing, Zhenyu; Huang, Xiaofeng; Deng, Junjun; Andersson, August; Fang, Wenzheng; Gustafsson, Örjan; Zhou, Jiabin; Du, Ke
Abstract: Regional haze over China has severe implications for air quality and regional climate. To effectively combat these effects the high uncertainties regarding the emissions from different sources needs to be reduced. In this paper, which is the third in a series on the sources of PM2.5 in pollution hotspot regions of China, we focus on the sources of black carbon aerosols (BC), using carbon isotope signatures. Four-season samples were collected at two key locations: Beijing-Tianjin-Hebei (BTH, part of Northern China plain), and the Pearl River Delta (PRD). We find that that fossil fuel combustion was the predominant source of BC in both BTH and PRD regions, accounting for 75 ± 5%. However, the contributions of what fossil fuel components were dominating differed significantly between BTH and PRD, and varied dramatically with seasons. Coal combustion is overall the all-important BC source in BTH, accounting for 46 ± 12% of the BC in BTH, with the maximum value (62%) found in winter. In contrast for the PRD region, liquid fossil fuel combustion (e.g., oil, diesel, and gasoline) is the dominant source of BC, with an annual mean value of 41 ± 15% and the maximum value of 55% found in winter. Region- and season-specific source apportionments are recommended to both accurately assess the climate impact of carbonaceous aerosol emissions and to effectively mitigate deteriorating air quality caused by carbonaceous aerosols. Highlights: The dual carbon isotopes are used to apportion BC sources over 4 seasons at 2 hotspots. Contributions of dominant fossil fuel components differed between sites and seasons. Coal combustion is the dominant BC source in Northern China in winter. Liquid fossil fuel combustion dominates BC emission in Southern China in summer. Air masses from Northern China could influence the BC composition in Southern China.